Peran Kepala Madrasah dalam Pengembangan Budaya Organisasi di Mts ‘Aisyiyah Sumatera Utara - Amiruddin Siahaan; Neliwati Neliwati; Sarah Lailatil Fadla (Al-Tarbiyah : Jurnal Ilmu Pendidikan Islam, 2024)
The research conducted here is entitled “The Role of Madrasa Heads in the Development of Organizational Culture in MTs ‘Aisyiyah North Sumatra”, with the background that lack of implementation of organizational culture in this madrasa. The research method uses a qualitative research type with a phenomenological approach. As a source of data for this research, the researcher took several sources of information from the head of the madrasa, the deputy head of the madrasa for curriculum, the deputy head of the madrasa for students affairs, one teacher, and also two student at MTs ‘Aisyiyah North Sumatra. The research result revealed that, 1) the role of the madrasa head in developing organizational culture at MTs ‘Aisyiyah North Sumatra, namley a) forming cooperative relationship, b) creating innovaion or renewal, and c) providing motivation; 2) implementing organizational culture development at MTs ‘Aisyiyah North Sumatra is implemented through three things, namely a) developing student caracter, b) developing student interests and talents, and c) developing student knowledge; 3) supporting and inhibiting factors for the implementation of organizational culture at MTs ‘Aisyiyah North Sumatra, namely a) supporting factors: the role of the madrasa head, cooperative relationships within the madrasa, the community that supports the implementation of organizational culture in the madrasa, and b) inhibiting factors: teachers who not being optimal in carrying out their roles, lack of awareness among students to implement organizational culture in madrasa, lack of facilities in madrasa, and lack of understanding of parents regarding the mplementation of organizational culture in the madrasa.